Osallistuminen aikuiskoulutukseen vuonna 2012 - Niemi, Helena; Ruuskanen, Timo; Seppänen, Tarja (Tilastokeskus, 2014)
Aikuiskoulutustutkimus 2012
Keywords: tilastot; koulutus; henkilöstökoulutus; aikuisopiskelu; kielitaito; tietotekniikka; Koulutus; Aikuiskoulutus